AVALIAÇÃO OBSERVACIONAL DA QUALIDADE DO PESCADO COMERCIALIZADO NO MUNICÍPIO DE NOVA IGUAÇU FRENTE À PANDEMIA POR SARS-COV-2 - BARBOSA, S. A.; FIGUEIRA, B. S.; SILVA, T. T.; BAPTISTA, L. S. B.; CABRAL, C. C.; SIMOES, J. S.; SOUZA, A. L. M. (Ars Veterinaria, 2021)
The pandemic caused by SARS-CoV-2 brought to society a health crisis that drastically affected the global economy and brought more restrictive measures to food supply establishments, which are classified as essential activities. However, they had to adapt to the new hygienic-sanitary operating protocol, established through regulations published by the Federal and State Governments in order to reduce the chances of viral spread. The objective of the study was to evaluate the hygienic and sanitary conditions of fish sold in fish markets in the city of Nova Iguaçu/RJ, through questionnaires on the application of good marketing and handling practices, during the lockdown related to the coronavirus pandemic. An observational "checklist" type questionnaire was used to assess the hygienic and sanitary conditions of fish in 13 fish markets located in 7 districts of Nova Iguaçu/RJ. It was observed that in 92% of the establishments visited had materials and equipment in disuse in the outdoor area, had failures in conservation, sanitation and adequate maintenance, without vector and pest control, without a suitable container for waste collection, lack of personal cleanliness and did not present the amount of flaky ice adequate to coat the fish. Thus, it was possible to check that the establishments did not follow the basic rules of hygiene and safety of the fish to reduce the dissemination of the coronavirus, confirming that the commercialization of fish in the fish markets visited in the municipality of Nova Iguaçu/RJ does not meet the recommended standards of hygiene and packaging of the products sold. Therefore, the relevance of this study is to provide fishmongers in the municipality of Nova Iguaçu, practical and viable guidelines for adapting to the legislation, with the main objective of updating and favoring the reinforcement of Good Handling Practices through an illustrative folder distributed later on visits to establishments.